SISTEM INFORMASI SERTIFIKASI HALAL MENGGUNAKAN CHATBOT (STUDI KASUS: BADAN PENYELENGGARA JAMINAN PRODUK HALAL) - Ilham Wardana (2024)
The Halal Product Assurance Organizing Agency (BPJPH) is a working unit formed under the Ministry of Religious Affairs of the Republic of Indonesia in accordance with the mandate of Law Number 33 of 2014 concerning Halal Product Assurance. BPJPH has a website containing information related to halal certification in Indonesia. However, the website's utilization has not been optimal in providing up-to-date information, requiring users to actively inquire to find the needed information. This research aims to develop a chatbot application that can assist in quickly answering user queries regarding halal certification in Indonesia. The method employed is a qualitative approach involving direct observation and interviews with BPJPH representatives. The "Halalbot" chatbot application is created using the waterfall system design method, and the algorithm used in designing and building the chatbot model is the Long Short- Term Memory (LSTM). The research stages include data collection and exploration, data preparation, building the "Halalbot" chatbot model using the LSTM method, model training using k-fold cross-validation, and system testing using blackbox testing. The testing results indicate an accuracy of 96.77%, signifying the effectiveness of the chatbot model in responding to questions regarding halal certification. These findings also support the use of the "Halalbot" chatbot as an information service at BPJPH, facilitating users in accessing halal certification information more easily and efficiently.